1982
DOI: 10.1083/jcb.93.2.463
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-fracture cytochemistry: partition of glycophorin in freeze-fractured human erythrocyte membranes.

Abstract: Thin-section and critical-point-dried fracture-labeled preparations are used to determine the distribution and partition of glycophorin-associated wheat germ agglutinin (WGA) binding sites over protoplasmic and exoplasmic faces of freeze-fractured human erythrocyte membranes. Most wheat germ agglutinin binding sites are found over exoplasmic faces . Label is sparse over the protoplasmic faces . These results contrast with previous observations of the partition of band 3 component where biochemical analysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
1

Year Published

1984
1984
1989
1989

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 18 publications
3
25
1
Order By: Relevance
“…They contrast with the images seen in mens, reorganization of freeze-fracture membrane halves re-suits in a rugose structure (Fig. 9) where membrane-intercalated particles are not identifiable (27,28,(41)(42)(43) . Observation of replicas of boar sperm flagella illustrated clearly the high density of both Con A and WGA receptors along protoplasmic membrane halves of the different segments of the sperm tail (Figs .…”
Section: Thin-section Fracture-labelcontrasting
confidence: 41%
See 3 more Smart Citations
“…They contrast with the images seen in mens, reorganization of freeze-fracture membrane halves re-suits in a rugose structure (Fig. 9) where membrane-intercalated particles are not identifiable (27,28,(41)(42)(43) . Observation of replicas of boar sperm flagella illustrated clearly the high density of both Con A and WGA receptors along protoplasmic membrane halves of the different segments of the sperm tail (Figs .…”
Section: Thin-section Fracture-labelcontrasting
confidence: 41%
“…As freeze-fracture splits biological membranes through its hydrophobic plane (46,47), we conclude that labeling on protoplasmic halves results from dragging, during fracture, of oligosaccharides of transmembrane glycoproteins across the outer (exoplasmic) half of the membrane. Previous comparisons on the partition of the major integral proteins of human erythrocytes with freezefracture membrane halves suggested the operation of a stochastic process that reflects the relative expression of each species of transmembrane protein at each side of the membrane as well as its interaction with components of the membrane skeleton (26,42) . We showed that glycophorin, preferentially expressed at the outer surface and without linkages to the membrane skeleton (48,49), partitions preferentially with the outer half of the erythrocyte membrane while band 3, which has a large hydrophilic segment exposed at the inner surface and known associations to the membrane skeleton (50,51), partitions preferentially with the inner half of the membrane (26,42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As freeze-fracture splits biomembranes along their bilayered continuum (17,18), fracture-label techniques can be used to determine the sidedness of membrane components and, in some instances, to identify transmembrane proteins as well as their regionalization along the plane of the membrane (19)(20)(21)(22)(23). Because labeling is done after freeze-fracture, fracture-label was not intended as a substitute for surface labeling.…”
mentioning
confidence: 99%